The Evolution of Taste in American Collecting - Brimo, Rene, 1911-1948 (Book collections on Project MUSE., 2016)
"A critical translation of Rene Brimo's 1938 French study of eighteenth- and nineteenth-century patronage and art collecting in the United States"--Provided by publisher.